2003
DOI: 10.1002/chem.200204621
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic L61 Accelerates Flip–Flop and Transbilayer Doxorubicin Permeation

Abstract: It has recently been found that Pluronics (block copolymers of ethylene oxide, EO, and propylene oxide, PO) favor the permeability and accumulation of anthracycline antibiotics, for example doxorubicin (Dox), in tumor cells. In an effort to understand these results, the interaction of EO(2)/PO(32)/EO(2) (Pluronic L61) with unilamellar egg yolk vesicles (80-100 nm in diameter) was examined. A partition coefficient K(p)=[Pl](membrane)/[Pl](water)=45 was determined. This corresponds to adsorption of about 20 poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 49 publications
7
53
0
Order By: Relevance
“…In fact, other studies demonstrated that while polyoxyethylene surfactants reversed MDR and also decreased lipid fluidity in plasma membrane vesicles from MDR cells, surfactants that did not reverse MDR did not influence membrane fluidity [149]. Moreover, low concentrations of Pluronic 61 were found to greatly increase the rates of phospholipid flip-flop and transbilayer movement of doxorubicin in lipid bilayers [150].…”
Section: Proteoliposomes As Tools To Study Mdr: the Case Of Pgpmentioning
confidence: 96%
“…In fact, other studies demonstrated that while polyoxyethylene surfactants reversed MDR and also decreased lipid fluidity in plasma membrane vesicles from MDR cells, surfactants that did not reverse MDR did not influence membrane fluidity [149]. Moreover, low concentrations of Pluronic 61 were found to greatly increase the rates of phospholipid flip-flop and transbilayer movement of doxorubicin in lipid bilayers [150].…”
Section: Proteoliposomes As Tools To Study Mdr: the Case Of Pgpmentioning
confidence: 96%
“…Increased uptake of polymeric micelles as a result of direct effects, such as increase in membrane permeability and/ or inhibition of P-gp efflux pump, has been reported (35). Membrane fluidity could also be affected, as demonstrated for pluronic micelles (40). Soluble amphiphiles, or detergents, are known to produce structural and dynamic effects on membranes, even at low concentrations.…”
Section: Bioavailability Analysismentioning
confidence: 98%
“…1). This is likely because surfactants such as Pluronics can fuse with the cell membranes, thus affecting their microviscosity, which leads to an enhancement of the transmembrane transport that is likely involved in the transfection mechanism [43]. Nanogels based on P85-g-PEI fused into the endosomal membrane, i.e., possessed distinct membranotropic features [42].…”
Section: Pluronic-polycation Conjugates: Structures and Colloidal Promentioning
confidence: 99%